Electronic Money, Materialism, And Social Media: The Triple Threat Reshaping Student Spending Habits - Rahardjo, Cahaya Jasmine; Yanto, Yanto; Supriaman, Supriaman (Universitas Muhammadiyah Ponorogo, 2025)
This study addresses the changing consumption patterns of university students driven by electronic money usage, materialistic values, and social media exposure, with the objective of examining how these factors influence student consumption behavior among students of the Faculty of Economics and Business at Tanjungpura University. Using a descriptive causal quantitative approach, data were collected through an online survey of 100 respondents and analyzed using Structural Equation Modeling (SEM) by AMOS. The research findings reveal that electronic money usage has no significant effect on consumption behavior. In contrast, materialism, social media intensity, and attitudes toward social media content had a significant beneficial effect on student consumption behavior. These results emphasize the importance of money management skill and financial inclusion strategies in shaping healthy consumption patterns and supporting sustainable development.